Translation and cross-cultural adaptation of the Integrated Palliative Care Outcome Scale in Hindi: Toward capturing palliative needs and concerns in Hindi speaking patients. (March 2023) - Bhardwaj, Tushti; Chambers, Rachel L; Watson, Harry; Srividya,; Higginson, Irene J; Hocaoglu, Mevhibe B
Background: Culturally relevant patient-centered outcomes tools are needed to identify the needs of patients and to assess their palliative care concerns. Aim: To translate and culturally adapt the Integrated Palliative Care Outcome Scale (IPOS) into Hindi. Design: The study applied a standardized methodology entailing six phases for translation and content validation: equivalence setting through a three-step process; forward translation; blind backward translation; expert review by a panel of the POS team; cognitive de-briefing with patients; and proof-reading of the final tool. All interviews and focus groups were audio-recorded, transcribed and analyzed using content analysis. Setting/participants: ( 1) Healthcare professionals including doctors, nurses, psychologists, counselors, and volunteers working in Indian palliative care settings with expertise in both English and Hindi languages; (2) Hindi speaking patients diagnosed with cancer who were receiving palliative care in community settings. Caregivers, palliative care experts, and language translators contributed to the translation procedure. Results: Phrases like nausea, poor appetite, drowsiness, and depression were difficult to translate into Hindi. Response categories "occasional" and "sometimes" were overlapping. All items, instructions and response categories were simple to understand. A visual thermometer is a unique feature of Hindi IPOS to facilitate responses from less educated patients. Conclusion: Hindi IPOS has face and content validity for use in clinical practice and research. The Hindi IPOS has implications beyond Indian palliative care settings. Millions of Hindi speakers can now respond to IPOS, and have a tool for communicating their palliative care needs in their mother tongue to inform patient-centered care.